Reframing organizations : artistry, choice, and leadership - Bolman, Lee G.; Deal, Terrence E. (San Francisco : Jossey-Bass Publishers, 1997)
Bolman and Deal consolidate key learnings from organization theory into four practical, easy-to-understand perspectives or "frames": structural, human resource, political, and symbolic. These frames provide a complete portrait of an organization and allow managers to clarify issues and create a flexible, dynamic, "big picture" management strategy. Using numerous examples from business, education, health care, and the public sector, the authors demonstrate how to integrate these four frames into a powerful and coherent strategy that can be applied to any organization. Drawing on a wealth of new material, fresh insights, and current examples, this more concise second edition of Reframing Organizations provides a sharp perspective on the rapidly changing business and political climate of the late 1990s.
1. Introduction: The Power of Reframing -- 2. Simple Ideas, Complex Organizations -- 3. Getting Organized -- 4. Structuring and Reengineering -- 5. Organizing Groups and Teams -- 6. People and Organizations -- 7. Improving Human Resource Management -- 8. Interpersonal and Group Dynamics -- 9. Power, Conflict, and Coalitions -- 10. The Manager as Politician -- 11. Organizations as Political Arenas and Political Agents -- 12. Organizational Culture and Symbols -- 13. Organization as Theater -- 14. Organizational Culture in Action -- 15. Integrating Frames for Effective Practice -- 16. Reframing in Action: Opportunities and Perils -- 17. Reframing Leadership -- 18. Reframing Change: Training, Realigning, Negotiating, Grieving -- 19. Reframing Ethics and Spirit -- 20. Bringing It All Together: Change Leadership in Action -- 21. Epilogue: Artistry, Choice, and Leadership.
Includes bibliographical references (p. 381-402) and indexes.
Keywords: Leadership; Management; Organizational behavior; Διοίκηση και οργάνωση.